Developing English Speaking Material through Contextual Teaching and Learning (CTL) for Beauty Study Program - Nilam Ulami Siregar; I Wayan Dirgeyasa; Rahmad Husein (LINGUISTIK TERAPAN, 2020)
The research was aimed to identify the target needs and learning needs of the tenth grade student of Beauty Study program at SMK Pariwisata Imelda Medan and to develop English speaking material through CTL for Beauty Study Program. This research was implemented by conducting Research and Development (R n D) study by Borg and Gall. There are four steps were done namely: (1) need analysis; (2) developing material; (3) evaluating and (final revision).  The target clients of this research were 34 people which consisted of (a) 30 students of Tenth grade of Beauty Program chosen by total random sampling technique; (b) English lectures; (c) English teacher; and (d) stakeholder. There were 3 types of technique for collecting the data applied in this research, they were questionnaire which used to gain the need analysis and validate the material, documentation consisted of the existing material, and interview to support the data gained from the previous techniques. The data of the research was analyzed descriptively. The result of this research were (1) the students needed the English speaking material which contains the material relating to their filed expertise and supported by innovative and creative learning process, and (2) the English speaking material developed through CTL is a set of English speaking material which consisted of 6 units.  Keywords: R and D, Speaking Material, Beauty Study, CTL